Cultural stigma, psychological distress and help-seeking: Moderating role of self-esteem and self-stigma in Lebanon - Myriam El Khoury-Malhame; Toni Sawma; Souheil Hallit; Chloe Joy Younis; Jad Jaber; Rita Doumit (PLoS ONE, 2025)
Background/Objective Mental illness is a common and often stigmatized condition. Stigma around mental illness refers to the negative attitudes and beliefs society holds about individuals with mental health conditions and can sometimes prevent those individuals from seeking adequate therapy. This study aims to explore the intricate relation between stigma, psychological distress, self-esteem, and help-seeking attitudes among young adults with diagnosed mental illnesses and further investigates the moderating effect of self-esteem and self-stigma. Method A cross-sectional online survey was shared via digital platforms between February 2023 and August 2024. A final sample of 245 participants with clinical mental health diagnoses, from predominantly bachelor-level backgrounds and located in different Lebanese regions, participated in the study and filled demographics data as well as assessments for stigma (Stigma Scale), self-esteem (Rosenberg Self-Esteem scale), help-seeking(Attitudes Towards Seeking Professional Psychological Help-short form (ATSPPH-SF)), distress (Kessler Psychological Distress scale (K6)), and self-stigma (Self-Stigma Questionnaire (SSQ)). Results Results revealed that self-esteem and self-stigma moderated the association between stigma, psychological distress, and help-seeking attitude. At low and moderate levels of self-esteem, higher psychological distress was significantly associated with lower help-seeking attitude, while at moderate and high levels of self-stigma, higher psychological distress was associated with lower help-seeking attitude. Conclusion Stigma remains a pervasive condition closely related to increased psychological suffering, decreased self-esteem and lower tendencies to seek help. These inaccurate beliefs and stereotypes are associated with overall discomfort in people with mental disorders perceived as unpredictable, impulsive, and dangerous. It is important for public policy makers within collectivist cultures to better address these misconceptions and promote help-seeking attitudes.